Boron‐Doped Diamond Functionalization by an Electrografting/Alkyne–Azide Click Chemistry Sequence. Issue 7 (24th June 2014) - Yeap, Weng Siang; Murib, Mohammed Sharif; Cuypers, Wim; Liu, Xianjie; van Grinsven, Bart; Ameloot, Marcel; Fahlman, Mats; Wagner, Patrick; Maes, Wouter; Haenen, Ken
Abstract A straightforward protocol for the covalent functionalization of boron‐doped diamond electrodes with either ferrocene or single‐stranded deoxyribonucleic acid (DNA) is reported. The functionalization method is based on a combination of diazonium salt electrografting and click chemistry. An azide‐terminated organic layer is first electrografted onto the diamond surface by electrochemical reduction of 4‐azidophenyldiazonium chloride. The azidophenyl‐modified surface then reacts rapidly and efficiently with molecules bearing a terminal alkyne moiety by means of CuI‐catalyzed alkyne–azide cycloaddition. Covalent attachment of ferrocene moieties was analyzed by X‐ray photoelectron spectroscopy and cyclic voltammetry, whereas impedance spectroscopy was applied for the characterization of the immobilized DNA.